Tools for accurate assessment of botrytis bunch rot (Botrytis cinerea) on wine grapes - Hill, G.N.; Beresford, R.M.; Evans, K.J. (New Zealand Plant Protection, 2010)
Botrytis bunch rot (botrytis) can reduce grape yield and wine quality Standardised assessment methods are needed to allow greater precision in wine making and to allow the use of disease management decision support models in grape production This study developed a botrytis disease assessment key to assist the accuracy of visual disease assessment Associated computer training software designed to improve the accuracy of disease assessments was also developed and tested The mean absolute error in estimates of percentage botrytis severity was significantly (P